GAMBARAN PERILAKU AGRESIF DITINJAU DARI PERSPEKTIF USIA DAN TINGKAT KELAS BAGI PESERTA DIDIK SMK - Agum Ahmad Sugian; Siti Fatimah; Reza Pahlevi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This research is based on phenomena in the field which show the aggressive behavior of students of SMK Negeri 1 Plered Purwakarta class XI. The purpose of this study was to determine the description of aggressive behavior, the factors causing aggressive behavior in terms of age and grade level perspective. Samples who behave aggressively are students who experience problems personally. This type of research uses descriptive quantitative methods aimed at revealing individual data. The research sample amounted to 82 people taken from the total population. Information collection is carried out to obtain data related to the phenomenon of circumstances, or certain variables and the presentation of conclusions through statistical exposure, data collection methods using questionnaires. Aggressive behavior is a reaction to conditions of worry, frustration, anger by trying to hurt others. The form of aggressive behavior in responding to a condition of worry, frustration, anger by attacking an object, physically attacking, symbolically or verbally threatening and degrading others and demanding behavior. The results of the study stated that the causes of aggressive behavior were social, personal, cultural factors, weather conditions, and mass media.Keywords: Aggressive Behavior, Age, Grade Level.